The determinants of racial disparities in obesity: baseline evidence from a natural experiment. (15th December 2021) - Durfee, Thomas; Myers, Samuel; Wolfson, Julian; DeMarco, Molly; Harnak, Lisa; Caspi, Caitlin
Abstract: This article uses baseline data from an observational study to estimate the determinants of racial and gender disparities in obesity. Samples of low-income workers in Minneapolis and Raleigh reveal that respondents in Minneapolis have lower body mass indices (BMIs) than respondents in Raleigh. There are large, statistically significant race and gender effects in estimates of BMI that explain most of the disparity between the two cities. Accounting for intersectionality—the joint impacts of being Black and a woman—reveals that almost all the BMI gaps between Black women in Minneapolis and Raleigh can be explained by age and education differences.